Penetration of fleroxacin and ciprofloxacin into skin blister fluid: a comparative study. - Lubowski, T J (1992)
The penetration of multiple-dose concentrations of oral fleroxacin (400 mg every 24 h) and ciprofloxacin (500 mg every 12 h) into skin blister fluid in 12 healthy volunteers was determined in a randomized crossover study. Serum, blister fluid, and paper disk samples were analyzed by large-plate microbiologic assay. The mean areas under the concentration-time curve (AUC) for serum were 88.6 and 18.2 micrograms.h/ml/70 kg for fleroxacin and ciprofloxacin, respectively. The mean AUC for blister fluid and paper disks were 71.2 and 15.0 micrograms.h/ml/70 kg and 77.8 and 15.4 micrograms.h/ml/70 kg for fleroxacin and ciprofloxacin, respectively. Calculated penetration into interstitial fluid ranged from 74 to 92% for fleroxacin and 56 to 96% for ciprofloxacin; penetration was calculated by using the ratio of maximum drug concentration or AUC in blister fluid and paper disks to maximum drug concentration or AUC in serum. There was no significant difference between fleroxacin and ciprofloxacin in the percent penetration into skin blister fluid.